Equivalent circuit model of molecular sensing in the ionic environment - Donggeun Lee; Lim hokyun; Lee Taikjin; KIM, JAE HUN; Lee, Seok; Sang-Kook Han; Yong-Sang Ryu; Kim Chulki (한국전기전자재료학회, 2019)
Measurement of binding kinetics between small molecules in real time remains challenging in biotechnology [1],[2],[3]. Its time-dependent evaluation is naturally affected by measurement conditions. For this, various components of the measurement setup should be considered such as pH condition of ionic environment, their concentrations of ligands and proteins, and the details of the structure of the transducer to use[4],[5],[6]. Here, we propose a circuit model of a FET based transducer including a supported lipid bilayer (SLB) to quantify its equivalent circuit parameters. For that we adopted Langmuir isotherm model and finally connected this model to our experimental results. This will pave a new way to analyse molecular sensing in physiological environments.